Studi Potensi Lactobacillus Rhamnosus A6 Hasil Isolasi Dari Air Susu Ibu Sebagai Starter Dalam Pembuatan Yoghurt - Pangan, Media (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 4 No 2 (2017): Media Ilmiah Teknologi Pangan, 2017)
The aim of this research was to determine the potential of Lactobacillus rhamnosus A6 isolated from breast milk as a starter in the manufacture of yoghurt. The random design uses for the research with one factor treatment using different types of starter such as Lactobacillus rhamnosus A6 as single starter, Streptococcus thermophilus and Lactobacillus bulgaricus , Lactobacillus rhamnosus A6 and Lactobacillus bulgaricus , Lactobacillus rhamnosus A6 and Streptococcus thermophilus , and Lactobacillus rhamnosus A6 with Streptococcus thermophilus and Lactobacillus bulgaricus. Milk was pasteurized at 80°C for 15 minutes and then added 6% starter culture according to the treatment. Each treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by ANOVA and if there was any difference followed by Duncan test (DMRT). The best treatment was Lactobacillus rhamnosus A6 with Streptococcus thermophilus and Lactobacillus bulgaricus with good characteristic 3,16% protein content; 3,74 x 10 6 CFU/ml total LAB; pH of 4,64; 0,53% total lactic acid; 408,3 mPas viscosity; color (white and like), aroma (acid and like), flavor (acid and like), texture (thick and like), and overall acceptance (like).